Conversa com Helder Macedo com a participação de Laura Cavalcanti Padilha (07/06/2013) - Souza, Adalberto de Oliveira; Silva, Marisa Correa; Teles, Marco Antonio Hruschka (Acta Scientiarum. Language and Culture, 2014)
Entrevista